2013
DOI: 10.1063/1.4813903
|View full text |Cite
|
Sign up to set email alerts
|

High-quality Bi2Te3 thin films grown on mica substrates for potential optoelectronic applications

Abstract: We report high-quality topological insulator Bi2Te3 thin films grown on muscovite mica substrates by molecular beam epitaxy. The topographic and structural analysis revealed that the Bi2Te3 thin films exhibited atomically smooth terraces over a large area and a high crystalline quality. Both weak antilocalization effect and quantum oscillations were observed in the magnetotransport of the relatively thin samples. A phase coherence length of 277 nm for a 6 nm thin film and a high surface mobility of 0.58 m2 V−1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
37
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 53 publications
(38 citation statements)
references
References 37 publications
(29 reference statements)
1
37
0
Order By: Relevance
“…The thickness was determined by measuring the height of a scratch made carefully on thin films with AFM in tapping mode. 13 The composition analysis was carried out at the FEI Quanta FE-SEM. The magnetic property measurement was performed using a SQUID magnetometer.…”
Section: Methodsmentioning
confidence: 99%
“…The thickness was determined by measuring the height of a scratch made carefully on thin films with AFM in tapping mode. 13 The composition analysis was carried out at the FEI Quanta FE-SEM. The magnetic property measurement was performed using a SQUID magnetometer.…”
Section: Methodsmentioning
confidence: 99%
“…This method resulted in films with a flatter morphology and reduced 3D growth defects than single-step TI growths. High-quality films have been grown on a number of different substrates including GaAs(001) [63], GaAs(111)B [36], GaN [105], graphene [65], amorphous fused silica [106], and mica (110) [86,107]. It is possible that adapting the two-step growth method will facilitate bulk insulating Bi2Te3 films on a wide variety of substrates.…”
Section: Bi 2 Tementioning
confidence: 99%
“…The film thickness can be easily controlled by changing the deposition parameters, including laser pulse energy, deposition temperature, and processing time. Many investigations have shown that TIs presents interesting van der Waals epitaxial growth behavior on single-crystalline substrate and amorphous surface such as SiO 2 substrate43, mica substrate44, and Al 2 O 3 substrate45. Therefore, it has the potential to grow TIs on any substrate including soft-substrate for saturable absorption applications.…”
mentioning
confidence: 99%